Discovering common pathogenetic processes between COVID-19 and tuberculosis by bioinformatics and system biology approach - Huang, Tengda; He, Jinyi; Zhou, Xinyi; Pan, Hongyuan; He, Fang; Du, Ao; Yu, Bingxuan; Jiang, Nan; Li, Xiaoquan; Yuan, Kefei; Wang, Zhen (Frontiers in Cellular and Infection Microbiology, 2023)
The coronavirus disease 2019 (COVID-19) pandemic, stemming from the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2), has persistently threatened the global health system. Meanwhile, the tuberculosis (TB) caused by Mycobacterium tuberculosis (M. tb) still continues to be endemic in various regions of the world. There is a certain degree of similarities between the clinical features of COVID-19 and TB, but the underlying common pathogenetic processes between COVID-19 and TB are not well understood.To elucidate the common pathogenetic processes between COVID-19 and TB, we implemented bioinformatics and systematic research to obtain shared pathways and molecular biomarkers. Here, the RNA-seq datasets (GSE196822 and GSE126614) are used to extract shared differentially expressed genes (DEGs) of COVID-19 and TB. The common DEGs were used to identify common pathways, hub genes, transcriptional regulatory networks and potential drugs.Results: A total of 96 common DEGs were selected for subsequent analyses.Functional enrichment analyses showed that viral genome replication and immune-related pathways collectively contributed to the development and progression of TB and COVID-19. Base the protein-protein interaction (PPI) network analysis, we identified 10 hub genes, including IFI44L, ISG15, MX1, IFI44, OASL, RSAD2, GBP1, OAS1, IFI6 and HERC5. Then, the transcription factor (TF)-genes interaction and microRNA (miRNA) -genes coregulatory network identified 61 TFs and 29 miRNAs. Notably, we identified ten potential drugs to treat TB and COVID-19, 3 namely suloctidil, prenylamine, acetohexamide, terfenadine, prochlorperazine, 3'-Azido-3'-deoxythymidine, chlorophyllin, etoposide, clioquinol and propofol.This research provides novel strategies and valuable references for the treatment of tuberculosis and COVID-19.